GATA1-mediated megakaryocyte differentiation and growth control can be uncoupled and mapped to different domains in GATA1. - Kuhl, C; Atzberger, A; Iborra, F; Nieswandt, B; Porcher, C; Vyas, P (2005)
The DNA-binding hemopoietic zinc finger transcription factor GATA1 promotes terminal megakaryocyte differentiation and restrains abnormal immature megakaryocyte expansion. How GATA1 coordinates these fundamental processes is unclear. Previous studies of synthetic and naturally occurring mutant GATA1 molecules demonstrate that DNA-binding and interaction with the essential GATA1 cofactor FOG-1 (via the N-terminal finger) are required for gene expression in terminally differentiating megakaryocytes and for platelet production. Moreover, acquired mutations deleting the N-terminal 84 amino acids are specifically detected in megakaryocytic leukemia in human Down syndrome patients. In this study, we have systematically dissected GATA1 domains required for platelet release and control of megakaryocyte growth by ectopically expressing modified GATA1 molecules in primary GATA1-deficient fetal megakaryocyte progenitors. In addition to DNA binding, distinct N-terminal regions, including residues in the first 84 amino acids, promote platelet release and restrict megakaryocyte growth. In contrast, abrogation of GATA1-FOG-1 interaction leads to loss of differentiation, but growth of blocked immature megakaryocytes is controlled. Thus, distinct GATA1 domains regulate terminal megakaryocyte gene expression leading to platelet release and restrain megakaryocyte growth, and these processes can be uncoupled.